Publisher Correction: Contrasting latitudinal patterns in phylogenetic diversity between woody and herbaceous communities - Massante, Jhonny C; Götzenberger, Lars; Takkis, Krista; Hallikma, Tiit; Kaasik, Ants; Laanisto, Lauri; Hutchings, Michael J; Gerhold, Pille (Scientific reports, 2019)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.